Ningaloo Marine Park management program best practice for whale shark (Rhincodon typus) conservation - Tyne, Julian A.; Raudino, Holly; Lester, Emily; Francis, Gemma; Barnes, Peter; Waples, Kelly (Frontiers in Conservation Science, 2025)
The predictable nature of whale shark (Rhincondon typus) aggregations around the world forms the basis for nature-based tourism. The Ningaloo Marine Park (NMP), Western Australia is one of those locations and a management program has been in place since 1993. Measuring the effectiveness of the management program is important to minimise potential impacts on the whale sharks. In NMP tour operator vessels are equipped with an Electronic Management System (EMS) to collect data during whale shark encounters. Using EMS data and associated images of identified whale sharks from the months of March to July between 2011 to 2019, Generalised Additive Mixed Models (GAMMs) and Generalised Linear Mixed Effect Models (GLMMs) assessed the variation in duration of whale shark encounters. Using EMS data from 2010 to 2023 we mapped the density distribution of all whale shark encounters to identify hotspots. From the 44,017 whale shark encounters between 2011 to 2019, 7585 involved 986 individuals. On average individual sharks were encountered 4.30 times per day (± SD 3.15), with a mean duration of 15.30 mins (± SD 13.17). In Tantabiddi, daily encounters, distance, Southern Oscillation Index (SOI), habitat and vessel were important in predicting the variation in encounter duration, whereas in Coral Bay daily encounters, encounter number, SOI, sex and vessel were important at predicting the variation in encounter duration. There was no evidence to suggest a significant variation in whale shark encounter duration between days after repeated encounters in Tantabiddi or Coral Bay. However, some individuals were repeatedly encountered in a day with a cumulative encounter duration up to 224 minutes. A significant negative relationship between encounter duration and number of daily encounters was identified for Tantabiddi -0.073, p-value < 0.001, Coral Bay -12.3, p-value < 0.001 and for NMP overall -0.083, p-value <0.001. A Gi* statistic identified significant whale shark encounter hotspots where commercial whale shark encounters occur in higher densities. Our findings support the best practice standard of the whale shark management program in the NMP, however the potential pressure of prolonged cumulative whale shark encounter durations, and the high density of the whale shark encounters in some areas warrants further investigation.